Palabrita de Granger: creación y edición de contenidos para una comunidad de jóvenes lectores - Hualpa Vega, Intabay Alexandra (2020)
Palabrita de Granger is an Instagram account that was born with the idea of reaching out to the community of young readers in Latin America, with the purpose of generate interaction with them and became a leading figure for this group. This report will describe how this process went, the content created for the main and secondary platforms, and the results achieved. In addition, networks in which the growth of the chosen community could be greater for the extension of the project, and the opportunity of its conversion into a character will be proposed.